1993
DOI: 10.1128/jb.175.12.3893-3896.1993
|View full text |Cite
|
Sign up to set email alerts
|

Copy number of the 16S rRNA gene in Rickettsia prowazekii

Abstract: The obligate intracellular parasite, Rickettsia prowazekii, is a slowly growing bacterium with a doubling time of 8 to 12 h. The copy number of the 16S rRNA gene in the rickettsial chromosome was determined to be one. Genomic DNA from R. prowazekii was digested either by a variety of restriction enzymes known not to cut at any site in the rickettsial 16S rRNA gene or by a combination of these noncutting enzymes and SmaI, which cuts the gene only once. Only one DNA fragment in these digests hybridized to a biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Single-band patterns consistent with the hypothesis that there are single copies of the 16s rRNA gene in R. bellii, R. prowazekii, and the SFG species Rickettsia montana were aIso obtained when genomic DNA restricted by either SphI or EcoRI was probed by using labeled R. bellii 16s rRNA. Results obtained previously for R. prowazekii also indicated that this organism has a single copy of the 16s rRNA (21).…”
Section: Resultsmentioning
confidence: 52%
“…Single-band patterns consistent with the hypothesis that there are single copies of the 16s rRNA gene in R. bellii, R. prowazekii, and the SFG species Rickettsia montana were aIso obtained when genomic DNA restricted by either SphI or EcoRI was probed by using labeled R. bellii 16s rRNA. Results obtained previously for R. prowazekii also indicated that this organism has a single copy of the 16s rRNA (21).…”
Section: Resultsmentioning
confidence: 52%
“…Neutralized genes are subject to mutational degradation (101). When genes required for the free-living mode are forfeited, the facultative symbiont has evolved into an obligate symbiont or an obligate parasite, with a coding capacity that can be extremely limited (70,71,72,94,147,170,172). For example, the obligate parasites of the genus Rickettsia, like mitochondria, have virtually no genes for amino acid or nucleoside biosynthesis, but their facultative parasitic relatives, the Bartonella spp., are fully able to produce these intermediates in their free-living mode (20; Andersson et al, unpublished data).…”
Section: Genome Degradationmentioning
confidence: 99%
“…5a). The sequence conservation between individual rRNA genes when multiple copies are present in the bacterial genome allows the detection of tandem genes using a combination of enzymes that do and do not cleave within the gene sequence (Pang & Winkler, 1993 BAC clones B7 (16S clone) and D3 (23S clone) were initially digested using enzymes that had a single cleavage site within the rRNA genes (EcoRI and PstI for 16S ; NcoI and HindIII for 23S). They were then digested a second time using enzymes that did not cut within the rRNA genes (BamHI, NotI, EcoRV and NdeI for 16S ; EcoRI, BamHI, NotI, EcoRV and NdeI for 23S).…”
Section: F R Rurangirwa and Othersmentioning
confidence: 99%
“…Deviations from the typical 16S-23S-5S operon structure are rare, with the exception of obligate intracellular bacteria with small ( 1n5 Mb) genomes. Alternative rRNA gene arrangements are characterized by very low copy numbers of the rRNA genes with loss of the classical operon structure (Pang & Winkler, 1993 ;Andersson et al, 1995). These atypical structures are hypothesized to have arisen from a progenitor with the classical multiple operon structure by mutation and then differential deletion of individual 16S, 23S or 5S rRNA genes (Andersson et al, 1995 ;Kurland & Andersson, 2000).…”
mentioning
confidence: 99%